Knowledge, attitude and practice among diabetic patients visiting a tertiary care hospital in Bangalore, Karnataka - Polineni, Vindhya; Acharya, Supriya (International Journal Of Community Medicine And Public Health, 2020)
Background: Diabetes mellitus is a chronic non-communicable disease which has become the epidemic of the 21st century. According to WHO 1.6 million deaths were estimated to be directly caused by diabetes in the year 2016 and attributed to be the seventh leading cause of death in the world. Objective of the study was to assess the knowledge, attitude, practice about diabetic care among the diabetic patient, and to assess the association between KAP of diabetic care and socio-demographic factors. Methods: Cross-sectional study was done with purposive sampling for 4 months, on 62 sample size. Data collection tool was the KAP questionnaire which was adapted a study by Herath HMM. Results: Out of 66 participants, 34 (51.5%) had good knowledge about diabetes, 27 (40.9%) and 5 had poor knowledge (7.6%), 16 had positive attitude about diabetes care (24.2%) and 50 (75.8%) had negative attitude, 47 had good practice about diabetes care (71.2%) and 19 (28.8%) of them had bad practice. Conclusions: Though majority of the study participants had good to moderate knowledge (92.4%), their attitude was negative (75.8%) and the knowledge level did not fully reflect into the attitude and practices (71.2%). This suggests there is a gap in the knowledge, attitude and practice.